7T versus 3T MR Angiography to Assess Unruptured Intracranial Aneurysms - Leemans, Eva (J Neuroimaging, 2020)
BACKGROUND AND PURPOSE: Aneurysm size and neck measurements are important for treatment decisions. The introduction of 7T magnetic resonance angiography (MRA) led to new possibilities assessing aneurysm morphology and flow due to the higher signal‐to‐noise ratio. However, it is unknown if the size measurements on 7T MRA are similar to those on the standard 3T MRA. This study aimed to compare aneurysm size measurements between 7T and 3T MRA. METHODS: We included 18 patients with 22 aneurysms who underwent both 3T and 7T MRA. Three acquisition protocols were compared: 3T time of flight (TOF), 7T TOF, and 7T contrast‐enhanced MRA. Each aneurysm on each protocol was measured by at least two experienced neuroradiologists. Subsequently, the differences were evaluated using scatterplots and the intraclass correlation coefficients (ICC) of agreement. RESULTS: There was a good agreement among the neuroradiologists for the height and width measurements (mean ICC: .78‐.93); the neck measurements showed a moderate agreement with a mean ICC of .57‐.72. Between the MR acquisition protocols, there was a high agreement for all measurements with a mean ICC of .81‐.96. Measurement differences between acquisition protocols (0‐2.9 mm) were in the range of the differences between the neuroradiologists (0‐3.6 mm). CONCLUSION: Our study showed that 7T MRA, both nonenhanced and contrast‐enhanced, has a high agreement in aneurysm size measurements compared to 3T. This suggests that 7T is useful for reliable aneurysm size assessment.